Penerapan Rating Scale Observasi Penerapan Rating Scale Observasional terhadap Keaktifan Mahasiswa PGMI dalam Diskusi Analisis Soal IPA - Destiana Puanda Ashari; Ikhlasul Ardi Nugroho; Anita Ekantini; Uun Febriyani; Yanti Kumala Sembiring; Waode Sitti Fatimah; Annisa Rifah Rahman (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop, validate, and examine the practicality of a rating-scale–based observation instrument designed to assess the activeness of PGMI students during science question analysis discussions. A quantitative descriptive approach was employed, involving 40 fifth-semester PGMI students. The instrument was developed based on learning activity theory and a multidimensional student engagement framework, consisting of 9 indicators and 27 items rated on a 1–4 scale. Content validity was evaluated by three experts using Aiken’s V index. At the same time, instrument practicality was assessed by five trained observers acting as instrument users through a user satisfaction questionnaire based on a 1–5 Likert scale. The results indicated very high content validity, with an average Aiken’s V value of 0.97, and excellent practicality, reflected by a mean user satisfaction score of 4.36 out of 5. The application of the instrument revealed that student activeness fell into the high category, with an average activity score of 89.70 (SD = 11.22), and 90% of students were classified as active to very active. These findings demonstrate that the developed observation instrument is valid and practical for evaluating student activity in discussion-based learning, particularly within teacher education contexts.